2020
DOI: 10.3390/foods9091183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Method of Drying of Five Varieties Grapes (Vitis vinifera L.) on the Bunch Stem on Physicochemical, Microbiological, and Sensory Quality

Abstract: The influence of the drying technique on certain quality attributes of dried grapes was analysed. Five varieties of grape were used in this study (Bezsemenné, Perlette, Vrboska, Beauty seedless, and Jakubské). All the varieties were dried using four methods: drying at 40 °C, combined drying (70, 65, and 60 °C), drying at 70 °C, and lyophilisation. The quality attributes such as total soluble solids, water activity, content of vitamin C, the colour parameters (L*, a*, b*), and microbiological (colony forming un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Keskin et al [35] stated that the vitamin C in different grape varieties ranges from 6.38 mg 100 g FW −1 (Katıkara variety) to 12.83 mg 100 g FW −1 (Isabella variety). Langová et al [36] reported that the concentration of vitamin C ranges from 0.0 to 0.58 mg 100 g −1 in different raisin varieties, such as Bezsemenné, Perlette, Vrboska, Beauty seedless, and Jakubské. These results are lower than those reported from the Gök Üzüm variety in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…Keskin et al [35] stated that the vitamin C in different grape varieties ranges from 6.38 mg 100 g FW −1 (Katıkara variety) to 12.83 mg 100 g FW −1 (Isabella variety). Langová et al [36] reported that the concentration of vitamin C ranges from 0.0 to 0.58 mg 100 g −1 in different raisin varieties, such as Bezsemenné, Perlette, Vrboska, Beauty seedless, and Jakubské. These results are lower than those reported from the Gök Üzüm variety in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding to dried food products, the color property was an element of controlling and standardizing the final product [16]. Surface color determination for quality evaluation based on visual grading by trained humans was a common practice in the production of dried banana.…”
Section: Effect Of Different Pre-treatment Methods On the Color Chang...mentioning
confidence: 99%
“…The main dietary sources of AsA for humans are fruits. The AsA contents of some fruits are organized, such as tomato, kiwifruit, orange, strawberry, carrot, sweet pepper, and so on (Table 1) [18][19][20][21][22][23][24][25][26][27][28][29][30]. Because of the important role of AsA in plants, in-depth studies have been carried out on the metabolic pathways of AsA in plants (Figure 1).…”
Section: Metabolic Pathway Of Ascorbic Acidmentioning
confidence: 99%